Moderate Conservative: Qatari Politics in the Context of the World Cup in 2022 - Mustapa, Hasan; Mandala, Iim; Leiza Novemberiani, Riska (Candidate: Jurnal Sains Politik, 2024)
Most Muslim countries appear to be insulated from world events due to their conservatism. Qatar was successful in combating this stigma. This country hosted the 2022 World Cup with great success. Despite the fact that it was accompanied by several polemics throughout its 2010 election. The nature of this research is qualitative. The purpose of this research is to determine the worth of Qatar's political conservatism in the context of the 2022 FIFA World Cup. The study's findings demonstrate that, while Islamic politics is monarchical in nature and deemed less democratic. However, this does not imply that it is rigid in reaction to rapid world events. Qatar has been successful in answering several topics such as human rights, the hostile Arab climate, and political conservatism at this great event held every four years. Qatar was able to polish its conservatism in politics in order to become more tolerant. Qatar is neither ultra-conservative nor liberal, as evidenced by its mild rejection of the LGBTQ movement and consumption of alcohol during the World Cup. This is founded on conservatism ideals such as commitment to belief (religious) values, a positive social class, a monarchical system that is beginning to open up, and is adaptable to global developments while maintaining the power of tradition. This is a moderate conservative value.